PERNIKAHAN BEDA AGAMA MENURUT HUKUM POSITIF DI INDONESIA (Antara Tuntutan Normatif dan Kepentingan Kemashlahatan) - Yustiloviani, Yustiloviani (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2015)
The Problem of inter-religion marriage had been appeared since the beginning of Islamic Civilization. Nowadays, it is most often discussed and placed as a burning issue in public discussion. But actually, there are three opinion viewed differently this problem. First, the opinion which always forbids us to inter-religion marriage in any reason; whether between a moslem (man) with a non-moslem woman or vice a versa. Second, the opinion which permints or allows us to do it in all condition. Third, the opinion which allows us to do it in a very limited condition; it requires a specific term and condition. This problem accured across the nation because of misinterpretation in understanding qur’an and hadith. In Indonesia, it has been regulated in (article No. 1/1974 and KHI) where it is forbidden to all citizen to do it.